INOVASI OLAHAN DAUN KELOR SEBAGAI PENCEGAHAN STUNTING DI DESA UBUNG - Yuniar, Azzuhkruf Dwi; Winarto, Rohman Tabah; Lestari, Ernia Ayu; Anggara, Naufal Sakhi; Qutub, Hardy Muzami; Nurbaya, Fitri; Rahmadani, Adivia Tri; Anggraini, Febby Putri; Armadani, Gita; Turmuzi, Tamim Usamah (Jurnal Wicara, 2025)
Community Service Program (KKN) is a form of community engagement activity carried out by universities. In the KKN program implemented in Ubung Village, Jonggat Sub-district, Central Lombok Regency, a group of students from the University of Mataram initiated a program utilizing moringa leaves (Moringa Oleifera) as a strategy to prevent stunting through food innovation. The objective of this activity was to increase community awareness of nutrition, particularly among housewives, while also introducing diversification of highly nutritious local food products. The methods of the program included (1) scientific visits to the village government, (2) socialization and counseling on stunting and balanced nutrition, and (3) demonstrations of processing moringa leaves into snack products, namely moringa sticks. The results of the activity showed an increase in community knowledge regarding the utilization of moringa leaves, improved skills of housewives in processing moringa leaves into healthy snacks, as well as a growing interest of children in consuming vegetables in the form of moringa sticks. Although there was a challenge in the form of reduced vitamin C content due to the frying process, moringa stick products remained highly nutritious, were favored by children, and showed potential to be developed into a home-based business. Therefore, this KKN activity successfully provided tangible contributions to stunting prevention, family economic empowerment, and the strengthening of local food security in Ubung Village.